MELATONIN SECRETION AND HYPERSOMNIA IN CHILDREN AND ADOLESCENTS AFTER CRANIOPHARYNGIOMA RESECTION - E. Yu. Il'ina; N. A. Strebkova; V. A. Peterkova ("Paediatrician" Publishers LLC, 2012)
Craniopharyngioma is a rare embryonic tumor of the chiasm-sellar region with low malignancy rate but high frequency of recurrence. In spite of the favorable outcome and satisfactory results of treatment the patients quality of life worsens due to complications associated with anatomic localization of craniopharyngioma close to the optic nerve, optic chiasm, hypophysis and hypothalamus. The development of hypothalamic obesity is observed in 25-60% of children and adolescents after surgical treatment of craniopharyngioma, which is usually accompanied with significant disturbances of circadian rhythm and has the most important influence on patients quality of life.